The new IASLC/ATS/ERS lung adenocarcinoma classification from a clinical perspective: current concepts and future prospects - Zugazagoitia, Jon; Enguita, Ana Belen; Nuñez, Juan Antonio; Iglesias, Lara; Ponce, Santiago (Journal of Thoracic Disease, 2014)
The new the International Association for the Study of Lung Cancer (IASLC)/the American Thoracic Society (ATS)/the European Respiratory Society (ERS) pathologic classification of lung cancer has markedly changed the pathologic diagnosis of lung adenocarcinoma. This classification deals with many aspects that directly affect clinical practice, and opens new gateways for future research. By means of a multidisciplinary approach, it differs significantly from the former 2004 the World Health Organization (WHO) classification, which was mainly written by pathologist. The present review, in line with the consensus article, is divided in two components: the diagnosis and classification of lung adenocarcinoma in resection specimens and the diagnosis of lung cancer in small biopsies and cytology. Resection specimens are currently classified according to the predominant histologic pattern after comprehensive subtyping in 5% increments. This approach has led to the addition of new pathologic subtypes [adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and micropapillary predominant adenocarcinoma)] and to the discontinuation of some heterogeneous entities included in the former 2004 WHO classification (mixed subtype adenocarcinoma and bronchioloalveolar carcinoma). Overall, these changes have resulted in a better stratification of lung adenocarcinoma tumors in more homogeneous morphologic, clinical and biological subgroups. Pathologic subtyping has demonstrated prognostic utility in resected stage I-III patients, and recent data support their predictive role for the benefit of adjuvant chemotherapy. Moreover, comprehensive pathologic subtyping may potentially affect TNM staging and surgical management or early-stage tumors. On the other hand, for the first time, the novel pathologic classification provides standardized terminology and diagnostic criteria of small biopsies and cytology. Criteria are proposed not only for adenocarcinoma but also for other histologies, but special emphasis was put on the distinction between adenocarcinoma and squamous-cell carcinoma due to its major clinical implications. This review outlines the main issues of the new lung adenocarcinoma classification from a clinical perspective. We describe the different pathologic subtypes in resection specimens, with their most relevant clinical implications. Further on, we address the new terminology and diagnostic criteria for lung adenocarcinomas in small specimens, oriented to their importance for the management and treatment of metastatic lung cancer patients. Finally, we discuss some unanswered questions and relevant issues for the near future.